(untitled) (Fiep Bulletin - online, 2014)
The object of this study was to investigate the behavior of glycemia in response to two sessions of resistance exercise, accomplished using two distinct intensities. Participating in this study were five men who were practicing veterans of this type of exercise, with ages between 19 and 25 years. They participated in two sets of exercise, one being three series of 8 to 10 maximum repetitions, with a rest of 1.5 minutes between the series, in 10 exercises for inferior members (G1), the other set with the same characteristics, but with only 60% of the weight of the previous set (G2). They had a glycemia measurement after at least three hours without eating and then consuming a snack consisting of 25g of carbohydrates and a glycemic index of 56. Thirty minutes after this snack, the glycemia was measured again, and soon after, they began the training session. Five new glycemic measurements were taken after every two exercises during the two sets. The instrument utilized was a portable glycosimetro, model Acucheck Advantage from the brand Roche. The data was treated discreetly and the differences between the averages of G1 and G2 were analyzed by means of the Wilcoxon test, for p<0,05. It can be observed that the glycemia decreased at the beginning of the exercise for G1 and G2, and afterwards, the values remained relatively the same for G2, but increased for G1 (98; 93,4; 100 e 104 mg/dl for G1 and 95,6; 90,6; 93,8; 90,2 e 92,4 mg/dl for G2). The glycemic values were always higher for G1 with statistic differences found in the last two measurements (0,04). It can be concluded that the intensity of the resistant exercise interfered in the glycemic behavior, with the highest serica concentration of glucose occurring in the most intense exercise.